(untitled) (Journal of Plant Disease Sciences, 2023)
The current study was conducted to investigate the nutritional and physiological needs of isolated from in Nagpur mandarin basal rot. Eight solid Ganoderma lucidum culture media were tested for mycelial growth, and results Ganoderma lucidum revealed that Potato Dextrose Agar (PDA) medium was promising over all other media as recorded 89.55 mm mycelia growth after seven days of inoculation (DAI).Sabouraud dextrose agar (SDA) showed weak (23.42 mm) growth when compared to other media.In regards of physiological studies, the results revealed that optimum growth of was supported by 25°C temperature Ganoderma lucidum (90.0mm), 95% and 100%relative humidity (90.0 mm), and an alternate cycle of light of 12 hours and 12 hours’ dark (87.21 mm).